Composite sludge dehydrating agent and preparation method thereof

By preparing composite sludge dehydrating agents, using technologies such as iron-based metal organic frames and polyacrylamide chains, the problem of poor dehydration effect of existing sludge dehydrating agents is solved, and efficient sludge dehydration and cost reduction are achieved.

CN119118477AActive Publication Date: 2024-12-13KAIWEIER ENVIRONMENTAL PROTECTION MATERIALS CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411324333.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2024-12-13
Estimated Expiration
2044-09-23

AI Technical Summary

Technical Problem

The dehydration effect of existing sludge dehydrating agents is poor and the amount is large, which affects the efficiency of sludge treatment.

Method used

Using the preparation method of composite sludge dehydrating agent, the iron-based metal organic frame and polyacrylamide chain are formed by reacting the composite carrier, terephthalic acid, ferric chloride hexahydrate and acryloyl chloride under specific conditions. Amino polysiloxane and cyclodextrin form positive and negative charges and hydrophobic properties on the surface, destroying the colloidal structure of the sludge and improving the dehydration effect.

Benefits of technology

It significantly improves the sludge dehydration effect, reduces the cost and volume of sludge treatment, and improves the dehydration efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a composite sludge dehydrating agent and a preparation method thereof, the dehydrating agent is prepared by polymerizing a modified monomer, a modified carrier, acrylamide, acryloyloxyethyl trimethyl ammonium chloride and sodium methallyl sulfonate and forming polyacrylamide on the surface of the modified carrier, and the surface of the dehydrating agent contains positive and negative charges. Positive charges can be combined with negatively-charged organic suspended solids, the negative charges can accelerate sinking of inorganic suspended solids, polyacrylamide on the surface contains organic silicon chain segments, the hydrophobic effect of the dehydrating agent can be improved, the water isolation effect is achieved while the suspended solids are adsorbed, and the surface contains an iron-based metal organic framework, so that the dehydrating agent is more environmentally-friendly. The stable structure of the extracellular polymeric substance of the sludge can be destroyed by compounding with surface positive charges, so that the organic matter is dispersed, the internal moisture is released, and meanwhile, the organic matter can be coated by a cyclodextrin cavity on the surface and an internal porous cavity, so that the sludge dewatering effect is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sludge dehydration, and in particular to a composite sludge dehydrating agent and a preparation method thereof. Background Art

[0002] Sludge dehydration is the first problem to be solved in sludge treatment. After dehydration, the moisture content of the sludge is reduced, and the volume is greatly reduced, which will reduce the scale and cost of subsequent sludge transportation, composting, and landfilling. Further dehydration treatments such as drying and incineration will also be more effective. However, due to the high hydrophilicity of sludge, the water contained in it is difficult to be directly removed mechanically, and sludge conditioning, that is, pre-treatment of sludge by chemical or physical methods, is an effective method. The principle of sludge conditioning is to change the physical and chemical properties of sludge particles, and by destroying the colloidal structure of the sludge, more bound water and free water are separated from the sludge particles to improve the dehydration performance. Chemical conditioning has the characteristics of simple operation and economical and effective, and has become a commonly used method at home and abroad. However, the existing sludge dehydrating agents have large input and poor dehydration effect, which affects the sludge treatment efficiency. Summary of the invention

[0003] The purpose of the present invention is to provide a composite sludge dehydrating agent and a preparation method thereof, which solves the problem that the dehydrating effect of the sludge dehydrating agent at the current stage is general and the dosage is large.

[0004] The purpose of the present invention can be achieved by the following technical solutions: A method for preparing a composite sludge dehydrating agent is prepared by the following steps: Step A1: the composite carrier, terephthalic acid, ferric chloride hexahydrate and DMF are mixed evenly, and the reaction is carried out for 20-25 hours at a speed of 150-200 r / min and a temperature of 80-85° C. to obtain a pretreated carrier; the pretreated carrier, acryloyl chloride, triethylamine and DMF are mixed evenly, and the reaction is carried out for 6-8 hours at a speed of 200-300 r / min and a temperature of 30-40° C. to obtain a modified carrier; Step A2: octamethylcyclotetrasiloxane, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, tetramethylammonium hydroxide and dimethyl sulfoxide are uniformly mixed, nitrogen is introduced for protection, and the reaction is carried out for 3-5 hours at a speed of 150-200 r / min and a temperature of 90-95° C. to obtain aminopolysiloxane; aminopolysiloxane, epoxybutene and DMF are uniformly mixed, and the reaction is carried out for 6-8 hours at a speed of 120-150 r / min, a temperature of 30-40° C. and a pH value of 11-12 to obtain a modified monomer; Step A3: uniformly mix the modified monomer, modified carrier, acrylamide, acryloyloxyethyl trimethyl ammonium chloride, sodium methyl propylene sulfonate and DMF, stir and add ammonium persulfate and 2,2'-azo (2-methylpropyl amidine) dihydrochloride at a speed of 150-200 r / min and a temperature of 20-25°C, raise the temperature to 40-50°C, react for 3-4 hours, and obtain a composite sludge dehydrating agent.

[0005] Furthermore, the mass ratio of the composite carrier, terephthalic acid and ferric chloride hexahydrate described in step A1 is 1:1:1.8, and the amount ratio of the pretreated carrier, acryloyl chloride and triethylamine is 1g:10mmol:10mmol.

[0006] Furthermore, the molar ratio of octamethylcyclotetrasiloxane, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and tetramethylammonium hydroxide described in step A2 is 1.2:1:1.5, and the molar ratio of aminopolysiloxane and epoxybutene is 1:4.

[0007] Furthermore, the amount ratio of the modified monomer, modified carrier, acrylamide, acryloyloxyethyl trimethyl ammonium chloride and sodium methacrylate sulfonate described in step A3 is 0.2 mol: 20 g: 9 mol: 1 mol: 1 mol, the amount of ammonium persulfate is 0.1% of the total mass of the modified monomer, acrylamide, acryloyloxyethyl trimethyl ammonium chloride and sodium methacrylate sulfonate, and the molar ratio of 2,2'-azo (2-methylpropyl amidine) dihydrochloride and ammonium persulfate is 1:1.

[0008] Furthermore, the composite carrier is prepared by the following steps: Step B1: lignin, sodium hydroxide, ethanol and deionized water are mixed evenly, stirred for 1-2 hours at a speed of 120-150 r / min and a temperature of 50-60° C., chloroacetic acid is added, the reaction is continued for 1-2 hours, the pH value is adjusted to be acidic, and carboxyl lignin is obtained. The carboxyl lignin is dispersed in toluene, KH550 and dicyclohexylcarbodiimide are added, and the reaction is carried out for 3-5 hours at a speed of 200-300 r / min and a temperature of 20-25° C. to obtain modified lignin; Step B2: Hexadecyltrimethylammonium bromide, deionized water, toluene, modified lignin and tetraethyl orthosilicate are mixed, stirred for 30-40 minutes at a speed of 800-1000 r / min and a temperature of 60-70°C, heated to 200-210°C, reacted for 3-5 hours, filtered to remove the filtrate, added the substrate to a muffle furnace, calcined for 2-3 hours at a temperature of 700-750°C under argon protection to obtain a precursor, dispersed the precursor in ethanol, stirred at a speed of 120-150 r / min and a temperature of 60-70°C, added KH550 and deionized water, reacted for 3-5 hours, and obtained a modified precursor; Step B3: β-cyclodextrin, epichlorohydrin, boron trifluoride etherate and DMF are mixed evenly, reacted at a speed of 120-150r / min and a temperature of 65-70°C for 2-3h, and then sodium hydroxide solution is added, the temperature is raised to 75-80°C, and the reaction is carried out for 3-5h to obtain modified cyclodextrin. The modified cyclodextrin, modified precursor and DMF are mixed evenly, reacted at a speed of 200-300r / min, a temperature of 30-40°C and a pH value of 10-11 for 3-5h, and then 2-aminoterephthalic acid is added and the reaction is continued for 3-5h to obtain a composite carrier.

[0009] Furthermore, the mass ratio of lignin, sodium hydroxide and chloroacetic acid in step B1 is 5:10:3, and the molar ratio of carboxyl groups on carboxyl lignin, KH550 and dicyclohexylcarbodiimide is 1:1:1.1.

[0010] Furthermore, the mass ratio of hexadecyltrimethylammonium bromide, modified lignin and tetraethyl orthosilicate in step B2 is 5:3:10, and the amount of KH550 used is 1% of the mass of the precursor.

[0011] Furthermore, the dosage ratio of β-cyclodextrin, epichlorohydrin, boron trifluoride etherate and sodium hydroxide solution in step B3 is 3g:1g:0.9g:15mL, the mass fraction of sodium hydroxide solution is 25%, and the mass ratio of modified cyclodextrin, modified precursor and 2-aminoterephthalic acid is 5:1:3.

[0012] The beneficial effects of the present invention are as follows: a composite sludge dehydrating agent prepared by the present invention uses a composite carrier, terephthalic acid and ferric chloride hexahydrate as raw materials, forms an iron-based metal organic framework on the surface of the composite carrier to prepare a pretreated carrier, reacts the pretreated carrier with acryloyl chloride so that the hydroxyl group on the pretreated carrier reacts with the acyl chloride on the acryloyl chloride, and grafts double bonds on the surface of the pretreated carrier to prepare a modified carrier, ring-opens octamethylcyclotetrasiloxane and polymerizes it with 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane to form an amino-terminated polysiloxane to prepare aminopolysiloxane, reacts the aminopolysiloxane with epoxybutene so that the amino group on the aminopolysiloxane reacts with the epoxy group on the epoxybutene to prepare a modified monomer, polymerizes the modified monomer, the modified carrier, acrylamide, acryloyloxyethyltrimethylammonium chloride and sodium methacrylic acid to form polyacrylamide on the surface of the modified carrier to prepare a dehydrating agent.

[0013] The composite carrier uses lignin and chloroacetic acid as raw materials. Under the action of sodium hydroxide solution, the hydroxyl group in the lignin molecule is converted into sodium hydroxyl, which then reacts with the chlorine atom site on the chloroacetic acid to obtain carboxyl lignin. Under the action of dicyclohexylcarbodiimide, the carboxyl group on the carboxyl lignin and the amino group on the KH550 are dehydrated to obtain modified lignin. The modified lignin is hydrothermally reacted with ethyl orthosilicate, and then calcined under argon protection conditions to convert the modified lignin into carbon tubes. At the same time, the surface is coated with porous diisocyanate. Silicon oxide is used to prepare a precursor, the precursor is treated with KH550 to graft amino groups on the surface to prepare a modified precursor, β-cyclodextrin is reacted with epichlorohydrin to react the epoxy group on the epichlorohydrin with the hydroxyl group on the β-cyclodextrin, and then a new epoxy group is formed by ring-closing under the action of sodium hydroxide solution to prepare a modified cyclodextrin, the modified cyclodextrin is reacted with the modified precursor to react the epoxy group on the modified cyclodextrin with the amino group on the modified precursor, 2-aminoterephthalic acid is added to react with the remaining epoxy group to prepare a composite carrier.

[0014] The surface of the dehydrating agent contains both positive and negative charges. The positive charge can combine with negatively charged organic suspended matter, and the negative charge can accelerate the sinking of inorganic suspended matter. The polyacrylamide on the surface contains silicone segments that can enhance the hydrophobic effect of the dehydrating agent, achieving a water-isolating effect while adsorbing suspended matter. The surface contains an iron-based metal organic framework, which, when combined with the positive charge on the surface, can destroy the stable structure of the sludge extracellular polymers, thereby dispersing the organic matter and releasing the internal moisture. At the same time, the organic matter can be coated by the cyclodextrin cavities on the surface and the porous cavities inside, further enhancing the sludge dehydration effect. DETAILED DESCRIPTION

[0015] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example

[0016] A method for preparing a composite sludge dehydrating agent is prepared by the following steps: Step A1: the composite carrier, terephthalic acid, ferric chloride hexahydrate and DMF are mixed evenly, and the reaction is carried out at a speed of 150 r / min and a temperature of 80° C. for 20 hours to obtain a pretreated carrier; the pretreated carrier, acryloyl chloride, triethylamine and DMF are mixed evenly, and the reaction is carried out at a speed of 200 r / min and a temperature of 30° C. for 6 hours to obtain a modified carrier; Step A2: octamethylcyclotetrasiloxane, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, tetramethylammonium hydroxide and dimethyl sulfoxide are uniformly mixed, nitrogen is introduced for protection, and the mixture is reacted for 3 hours at a speed of 150 r / min and a temperature of 90° C. to obtain aminopolysiloxane; aminopolysiloxane, epoxybutene and DMF are uniformly mixed, and the mixture is reacted for 6 hours at a speed of 120 r / min, a temperature of 30° C. and a pH value of 11-12 to obtain a modified monomer; Step A3: The modified monomer, the modified carrier, acrylamide, acryloyloxyethyl trimethyl ammonium chloride, sodium methyl propylene sulfonate and DMF were mixed evenly, and ammonium persulfate and 2,2'-azo (2-methylpropyl amidine) dihydrochloride were added under stirring at a speed of 150 r / min and a temperature of 20°C, and the temperature was raised to 40°C, and the reaction was carried out for 3 hours to obtain a composite sludge dewatering agent.

[0017] The mass ratio of the composite carrier, terephthalic acid and ferric chloride hexahydrate described in step A1 is 1:1:1.8, and the amount ratio of the pretreated carrier, acryloyl chloride and triethylamine is 1g:10mmol:10mmol.

[0018] The molar ratio of octamethylcyclotetrasiloxane, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and tetramethylammonium hydroxide in step A2 is 1.2:1:1.5, and the molar ratio of aminopolysiloxane and epoxybutene is 1:4.

[0019] The amount ratio of the modified monomer, modified carrier, acrylamide, acryloyloxyethyl trimethyl ammonium chloride and sodium methacrylate sulfonate described in step A3 is 0.2 mol: 20 g: 9 mol: 1 mol: 1 mol, the amount of ammonium persulfate is 0.1% of the total mass of the modified monomer, acrylamide, acryloyloxyethyl trimethyl ammonium chloride and sodium methacrylate sulfonate, and the molar ratio of 2,2'-azo (2-methylpropyl amidine) dihydrochloride and ammonium persulfate is 1:1.

[0020] The composite carrier is prepared by the following steps: Step B1: lignin, sodium hydroxide, ethanol and deionized water were mixed evenly, stirred for 1 hour at a speed of 120 r / min and a temperature of 50°C, chloroacetic acid was added, the reaction was continued for 1 hour, the pH value was adjusted to be acidic, and carboxyl lignin was obtained. The carboxyl lignin was dispersed in toluene, KH550 and dicyclohexylcarbodiimide were added, and the reaction was carried out for 3 hours at a speed of 200 r / min and a temperature of 20°C to obtain modified lignin; Step B2: Hexadecyltrimethylammonium bromide, deionized water, toluene, modified lignin and tetraethyl orthosilicate are mixed, stirred for 30 minutes at a speed of 800 r / min and a temperature of 60°C, heated to 200°C, reacted for 3 hours, filtered to remove the filtrate, added the substrate to a muffle furnace, calcined for 2 hours at a temperature of 700°C under argon protection to obtain a precursor, dispersed the precursor in ethanol, stirred at a speed of 120 r / min and a temperature of 60°C, added KH550 and deionized water, reacted for 3 hours, and obtained a modified precursor; Step B3: β-cyclodextrin, epichlorohydrin, boron trifluoride etherate and DMF are mixed evenly, reacted at a speed of 120 r / min and a temperature of 65°C for 2 hours, then sodium hydroxide solution is added, the temperature is raised to 75°C, and the reaction is carried out for 3 hours to obtain modified cyclodextrin; the modified cyclodextrin, modified precursor and DMF are mixed evenly, reacted at a speed of 200 r / min, a temperature of 30°C and a pH value of 10 for 3 hours, then 2-aminoterephthalic acid is added and the reaction is continued for 3 hours to obtain a composite carrier.

[0021] The mass ratio of lignin, sodium hydroxide and chloroacetic acid in step B1 is 5:10:3, and the molar ratio of carboxyl groups on carboxyl lignin, KH550 and dicyclohexylcarbodiimide is 1:1:1.1.

[0022] The mass ratio of hexadecyltrimethylammonium bromide, modified lignin and tetraethyl orthosilicate described in step B2 is 5:3:10, and the amount of KH550 used is 1% of the mass of the precursor.

[0023] The dosage ratio of β-cyclodextrin, epichlorohydrin, boron trifluoride etherate and sodium hydroxide solution described in step B3 is 3g:1g:0.9g:15mL, the mass fraction of sodium hydroxide solution is 25%, and the mass ratio of modified cyclodextrin, modified precursor and 2-aminoterephthalic acid is 5:1:3. Example

[0024] A method for preparing a composite sludge dehydrating agent is prepared by the following steps: Step A1: the composite carrier, terephthalic acid, ferric chloride hexahydrate and DMF are mixed evenly, and the reaction is carried out at a speed of 150 r / min and a temperature of 85° C. for 23 hours to obtain a pretreated carrier; the pretreated carrier, acryloyl chloride, triethylamine and DMF are mixed evenly, and the reaction is carried out at a speed of 200 r / min and a temperature of 35° C. for 7 hours to obtain a modified carrier; Step A2: octamethylcyclotetrasiloxane, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, tetramethylammonium hydroxide and dimethyl sulfoxide are uniformly mixed, nitrogen is introduced for protection, and the mixture is reacted for 4 hours at a speed of 150 r / min and a temperature of 90° C. to obtain aminopolysiloxane; aminopolysiloxane, epoxybutene and DMF are uniformly mixed, and the mixture is reacted for 7 hours at a speed of 120 r / min, a temperature of 35° C. and a pH value of 11 to obtain a modified monomer; Step A3: The modified monomer, modified carrier, acrylamide, acryloyloxyethyl trimethyl ammonium chloride, sodium methyl propylene sulfonate and DMF were mixed evenly, and ammonium persulfate and 2,2'-azo (2-methylpropyl amidine) dihydrochloride were added under stirring at a speed of 150 r / min and a temperature of 23°C. The temperature was raised to 45°C, and the reaction was carried out for 3.5 hours to obtain a composite sludge dewatering agent.

[0025] The mass ratio of the composite carrier, terephthalic acid and ferric chloride hexahydrate described in step A1 is 1:1:1.8, and the amount ratio of the pretreated carrier, acryloyl chloride and triethylamine is 1g:10mmol:10mmol.

[0026] The molar ratio of octamethylcyclotetrasiloxane, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and tetramethylammonium hydroxide in step A2 is 1.2:1:1.5, and the molar ratio of aminopolysiloxane and epoxybutene is 1:4.

[0027] The amount ratio of the modified monomer, modified carrier, acrylamide, acryloyloxyethyl trimethyl ammonium chloride and sodium methacrylate sulfonate described in step A3 is 0.2 mol: 20 g: 9 mol: 1 mol: 1 mol, the amount of ammonium persulfate is 0.1% of the total mass of the modified monomer, acrylamide, acryloyloxyethyl trimethyl ammonium chloride and sodium methacrylate sulfonate, and the molar ratio of 2,2'-azo (2-methylpropyl amidine) dihydrochloride and ammonium persulfate is 1:1.

[0028] The composite carrier is prepared by the following steps: Step B1: lignin, sodium hydroxide, ethanol and deionized water were mixed evenly, stirred for 1.5 hours at a speed of 120 r / min and a temperature of 55° C., chloroacetic acid was added, and the reaction was continued for 1.5 hours. The pH value was adjusted to be acidic to obtain carboxyl lignin, and the carboxyl lignin was dispersed in toluene, KH550 and dicyclohexylcarbodiimide were added, and the reaction was carried out for 45 hours at a speed of 200 r / min and a temperature of 20° C. to obtain modified lignin; Step B2: Hexadecyltrimethylammonium bromide, deionized water, toluene, modified lignin and tetraethyl orthosilicate are mixed, stirred for 35 minutes at a speed of 800 r / min and a temperature of 65°C, heated to 205°C, reacted for 4 hours, filtered to remove the filtrate, added the substrate to a muffle furnace, calcined for 2.5 hours at a temperature of 730°C under argon protection to obtain a precursor, dispersed the precursor in ethanol, stirred at a speed of 120 r / min and a temperature of 65°C, added KH550 and deionized water, reacted for 4 hours, and obtained a modified precursor; Step B3: β-cyclodextrin, epichlorohydrin, boron trifluoride etherate and DMF are mixed evenly, reacted at a speed of 120 r / min and a temperature of 68°C for 2.5 hours, and then sodium hydroxide solution is added, the temperature is raised to 78°C, and the reaction is carried out for 4 hours to obtain modified cyclodextrin. The modified cyclodextrin, modified precursor and DMF are mixed evenly, reacted at a speed of 200 r / min, a temperature of 35°C and a pH value of 11 for 4 hours, and then 2-aminoterephthalic acid is added and the reaction is continued for 4 hours to obtain a composite carrier.

[0029] The mass ratio of lignin, sodium hydroxide and chloroacetic acid in step B1 is 5:10:3, and the molar ratio of carboxyl groups on carboxyl lignin, KH550 and dicyclohexylcarbodiimide is 1:1:1.1.

[0030] The mass ratio of hexadecyltrimethylammonium bromide, modified lignin and tetraethyl orthosilicate described in step B2 is 5:3:10, and the amount of KH550 used is 1% of the mass of the precursor.

[0031] The dosage ratio of β-cyclodextrin, epichlorohydrin, boron trifluoride etherate and sodium hydroxide solution described in step B3 is 3g:1g:0.9g:15mL, the mass fraction of sodium hydroxide solution is 25%, and the mass ratio of modified cyclodextrin, modified precursor and 2-aminoterephthalic acid is 5:1:3. Example

[0032] A method for preparing a composite sludge dehydrating agent is prepared by the following steps: Step A1: the composite carrier, terephthalic acid, ferric chloride hexahydrate and DMF are mixed evenly, and the reaction is carried out at a speed of 200 r / min and a temperature of 85° C. for 25 hours to obtain a pretreated carrier; the pretreated carrier, acryloyl chloride, triethylamine and DMF are mixed evenly, and the reaction is carried out at a speed of 300 r / min and a temperature of 40° C. for 8 hours to obtain a modified carrier; Step A2: octamethylcyclotetrasiloxane, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, tetramethylammonium hydroxide and dimethyl sulfoxide are uniformly mixed, nitrogen is introduced for protection, and the reaction is carried out for 5 hours at a speed of 200 r / min and a temperature of 95° C. to obtain aminopolysiloxane; aminopolysiloxane, epoxybutene and DMF are uniformly mixed, and the reaction is carried out for 8 hours at a speed of 150 r / min, a temperature of 40° C. and a pH value of 12 to obtain a modified monomer; Step A3: The modified monomer, the modified carrier, acrylamide, acryloyloxyethyl trimethyl ammonium chloride, sodium methyl propylene sulfonate and DMF were mixed evenly, and ammonium persulfate and 2,2'-azo (2-methylpropyl amidine) dihydrochloride were added under stirring at a speed of 200 r / min and a temperature of 25°C. The temperature was raised to 50°C, and the reaction was carried out for 4 hours to obtain a composite sludge dewatering agent.

[0033] The mass ratio of the composite carrier, terephthalic acid and ferric chloride hexahydrate described in step A1 is 1:1:1.8, and the amount ratio of the pretreated carrier, acryloyl chloride and triethylamine is 1g:10mmol:10mmol.

[0034] The molar ratio of octamethylcyclotetrasiloxane, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and tetramethylammonium hydroxide in step A2 is 1.2:1:1.5, and the molar ratio of aminopolysiloxane and epoxybutene is 1:4.

[0035] The amount ratio of the modified monomer, modified carrier, acrylamide, acryloyloxyethyl trimethyl ammonium chloride and sodium methacrylate sulfonate described in step A3 is 0.2 mol: 20 g: 9 mol: 1 mol: 1 mol, the amount of ammonium persulfate is 0.1% of the total mass of the modified monomer, acrylamide, acryloyloxyethyl trimethyl ammonium chloride and sodium methacrylate sulfonate, and the molar ratio of 2,2'-azo (2-methylpropyl amidine) dihydrochloride and ammonium persulfate is 1:1.

[0036] The composite carrier is prepared by the following steps: Step B1: lignin, sodium hydroxide, ethanol and deionized water were mixed evenly, stirred for 2 hours at a speed of 150 r / min and a temperature of 60°C, chloroacetic acid was added, and the reaction was continued for 2 hours, and the pH value was adjusted to be acidic to obtain carboxyl lignin, the carboxyl lignin was dispersed in toluene, KH550 and dicyclohexylcarbodiimide were added, and the reaction was carried out for 5 hours at a speed of 300 r / min and a temperature of 25°C to obtain modified lignin; Step B2: Hexadecyltrimethylammonium bromide, deionized water, toluene, modified lignin and tetraethyl orthosilicate are mixed, stirred for 40 minutes at a speed of 1000 r / min and a temperature of 70°C, heated to 210°C, reacted for 5 hours, filtered to remove the filtrate, added the substrate to a muffle furnace, calcined for 3 hours at a temperature of 750°C under argon protection to obtain a precursor, dispersed the precursor in ethanol, stirred at a speed of 150 r / min and a temperature of 70°C, added KH550 and deionized water, reacted for 5 hours, and obtained a modified precursor; Step B3: β-cyclodextrin, epichlorohydrin, boron trifluoride etherate and DMF are mixed evenly, reacted at a speed of 150 r / min and a temperature of 70°C for 3 hours, then sodium hydroxide solution is added, the temperature is raised to 80°C, and the reaction is carried out for 5 hours to obtain modified cyclodextrin; the modified cyclodextrin, modified precursor and DMF are mixed evenly, reacted at a speed of 300 r / min, a temperature of 40°C and a pH value of 1 for 5 hours, then 2-aminoterephthalic acid is added and the reaction is continued for 5 hours to obtain a composite carrier.

[0037] The mass ratio of lignin, sodium hydroxide and chloroacetic acid in step B1 is 5:10:3, and the molar ratio of carboxyl groups on carboxyl lignin, KH550 and dicyclohexylcarbodiimide is 1:1:1.1.

[0038] The mass ratio of hexadecyltrimethylammonium bromide, modified lignin and tetraethyl orthosilicate described in step B2 is 5:3:10, and the amount of KH550 used is 1% of the mass of the precursor.

[0039] The dosage ratio of β-cyclodextrin, epichlorohydrin, boron trifluoride etherate and sodium hydroxide solution described in step B3 is 3g:1g:0.9g:15mL, the mass fraction of sodium hydroxide solution is 25%, and the mass ratio of modified cyclodextrin, modified precursor and 2-aminoterephthalic acid is 5:1:3.

[0040] Comparative Example 1 Compared with Example 1, this comparative example uses a composite carrier instead of the pre-treated carrier, and the other steps are the same.

[0041] Comparative Example 2 Compared with Example 1, no modified monomer was added in this comparative example, and the remaining steps were the same.

[0042] Comparative Example 3 Compared with Example 1, no modified carrier was added in this comparative example, and the remaining steps were the same.

[0043] Comparative Example 4 Compared with Example 1, no composite carrier was added in this comparative example, and the remaining steps were the same.

[0044] Comparative Example 5 Compared with Example 1, this comparative example uses a modified precursor instead of a modified carrier, and the remaining steps are the same.

[0045] Take 100g of sludge with a water content of 97.8%, a pH of 6.8, a Zeta potential of -23.7mv, and an organic matter content of 43.6%. Add the sludge dehydrating agents prepared in Examples 1-3 and Comparative Examples 1-5 respectively, and the amount of the sludge dehydrating agent is 10mg / g. Stir for 30s at a speed of 400r / min, and then stir for 5min at 150r / min. Measure the sludge specific resistance and the moisture content of the mud cake. The test results are shown in the following table.

[0046]

[0047] It can be seen from the above table that this application has a very good sludge dewatering effect.

[0048] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A method for preparing a composite sludge dehydrating agent, characterized in that: Made by the following steps: Step A1: mixing a composite carrier, terephthalic acid, ferric chloride hexahydrate and DMF to obtain a pretreated carrier, and mixing the pretreated carrier, acryloyl chloride, triethylamine and DMF to obtain a modified carrier; Step A2: octamethylcyclotetrasiloxane, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, tetramethylammonium hydroxide and dimethyl sulfoxide are mixed and reacted to obtain aminopolysiloxane, and aminopolysiloxane, epoxybutene and DMF are mixed and reacted to obtain a modified monomer; Step A3: the modified monomer, the modified carrier, acrylamide, acryloyloxyethyl trimethylammonium chloride, sodium methyl propylene sulfonate and DMF are mixed and stirred, and ammonium persulfate and 2,2'-azo (2-methylpropyl amidine) dihydrochloride are added, and the temperature is raised to react to obtain a composite sludge dehydrating agent.

2. The method for preparing a composite sludge dehydrating agent according to claim 1, characterized in that: The mass ratio of the composite carrier, terephthalic acid and ferric chloride hexahydrate described in step A1 is 1:1:1.8, and the amount ratio of the pretreated carrier, acryloyl chloride and triethylamine is 1g:10mmol:10mmol.

3. The method for preparing a composite sludge dehydrating agent according to claim 1, characterized in that: The molar ratio of octamethylcyclotetrasiloxane, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and tetramethylammonium hydroxide in step A2 is 1.2:1:1.5, and the molar ratio of aminopolysiloxane and epoxybutene is 1:

4.

4. The method for preparing a composite sludge dehydrating agent according to claim 1, characterized in that: The usage ratio of the modified monomer, modified carrier, acrylamide, acryloyloxyethyltrimethylammonium chloride and sodium methyl propylene sulfonate described in step A3 is 0.2 mol:20 g:9 mol:1 mol:1 mol.

5. The method for preparing a composite sludge dehydrating agent according to claim 1, characterized in that: The composite carrier is prepared by the following steps: Step B1: After mixing lignin, sodium hydroxide, ethanol and deionized water, chloroacetic acid is added and the reaction is continued to obtain carboxyl lignin, the carboxyl lignin is dispersed in toluene, KH550 and dicyclohexylcarbodiimide are added and reacted to obtain modified lignin; Step B2: Hexadecyltrimethylammonium bromide, deionized water, toluene, modified lignin and tetraethyl orthosilicate are mixed and stirred, and after heating to react, the filtrate is filtered to remove the filtrate, and the substrate is added to a muffle furnace for roasting to obtain a precursor, and the precursor is dispersed in ethanol, stirred, and KH550 and deionized water are added to react to obtain a modified precursor; Step B3: After β-cyclodextrin, epichlorohydrin, boron trifluoride etherate and DMF are mixed and reacted, sodium hydroxide solution is added, and the temperature is increased to react to obtain modified cyclodextrin. After the modified cyclodextrin, modified precursor and DMF are mixed and reacted, 2-aminoterephthalic acid is added and the reaction is continued to obtain a composite carrier.

6. The method for preparing a composite sludge dehydrating agent according to claim 5, characterized in that: The mass ratio of lignin, sodium hydroxide and chloroacetic acid in step B1 is 5:10:3, and the molar ratio of carboxyl groups on carboxyl lignin, KH550 and dicyclohexylcarbodiimide is 1:1:1.

1.

7. The method for preparing a composite sludge dehydrating agent according to claim 5, characterized in that: The mass ratio of hexadecyltrimethylammonium bromide, modified lignin and tetraethyl orthosilicate described in step B2 is 5:3:10, and the amount of KH550 used is 1% of the mass of the precursor.

8. The method for preparing a composite sludge dehydrating agent according to claim 5, characterized in that: The dosage ratio of β-cyclodextrin, epichlorohydrin, boron trifluoride etherate and sodium hydroxide solution in step B3 is 3g:1g:0.9g:15mL, and the mass ratio of modified cyclodextrin, modified precursor and 2-aminoterephthalic acid is 5:1:

3.

9. A composite sludge dehydrating agent, characterized in that: Prepared according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Composite macromolecular sludge dehydrating agent and preparation method thereof

    CN104004130A

  • High-molecular chitosan composite flocculant

    CN106673165A

  • Biochar recyclable sewage treatment agent and preparation method thereof

    CN117205901A

  • Recyclable sewage treatment agent and preparation method thereof

    CN118236984A

  • Organic sludge dehydrating agent

    CN118439776A